Case report: Maintaining altered states of consciousness over repeated ketamine infusions may be key to facilitate long-lasting antidepressant effects: some initial lessons from a personalized-dosing single-case study - Reissmann, Steffen; Hartmann, Matthias; Kist, Andreas; Liechti, Matthias E.; Stocker, Kurt (Frontiers in Psychiatry, 2023)
The interest in psychoactive agents for treating mental disorders has gathered a growing body of scientific interest. However, research on the relationship between altered states of consciousness (ASCs) and ketamine’s antidepressant properties is still limited. Likewise, approaches to sustain early treatment success for the long-term are needed. Taking both aspects into account, the question arises whether the persistence of recurrent ASCs during the subsequent infusion sessions is crucial for the preservation of antidepressant effects during prolonged continued ketamine therapy. In this case study we explored whether recurrent ASC experiences across a large number of infusions are associated with improved antidepressant effects in a single case study. A 62-year-old patient with treatment-resistant depression, who has been suffering from depressive episodes for over 20 years, was observed for 12 consecutive infusions across 16 weeks. ASCs during ketamine sessions were measured with the 5D-ASC, and pre/post-infusion depression scores with the BDI-II questionnaire. To emphasize psychoactive experiences a personalized antidepressant dose regimen was used. We found a strong correlation between the experienced ASCs during ketamine infusions and the antidepressant effect: the stronger the ASCs overall, the stronger the resulting antidepressant effect. This correlation was consistently observed throughout the infusion series, independent of the number of ketamine sessions completed before. However, despite a personalized dose regimen, neither peri-infusion ASCs nor antidepressant effects could be established on a regular basis, leading overall to no improvement in treatment outcome. Maintaining psychoactive effects over repeated ketamine infusions may be key to facilitate long-lasting antidepressant effects. However, for some depressed individuals maintenance of antidepressant effects and/or peri-infusion ASCs might not be achieved, even when personalized dosing is used.